2023
DOI: 10.1002/adfm.202307109
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Crystalline/Amorphous Heterostructure MoNi/NiMoOx for Electrochemical Hydrogen Evolution with Industry‐Level Activity and Stability

Xiaoyun Shi,
Xiaozhong Zheng,
Hao Wang
et al.

Abstract: The design of cheap, efficient, and durable electrocatalysts for high‐throughput H2 production is critical to give impetus to hydrogen production from fundamental to practical industrial applications. Here, a hierarchical heterostructure hydrogen evolution reaction (HER) electrocatalyst (MoNi/NiMoOx) with 0D MoNi nanoalloys nanoparticles embedded on well‐assembled 1D porous NiMoOx microrods in situ grown on 3D nickel foam (NF) is successfully constructed. The synergetic effect of different building units in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 74 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…38,39 To address this challenge, our group synthesized a 0D/1D hierarchical heterostructure (MoNi/NiMnO x on a 3D porous NF) to enhance the efficiency of the hydrogen evolution reaction. 40 The catalyst effectively manages bubbles, displaying smaller and more rapidly dispersed H 2 bubbles than Pt/C (Figure 5e). The 1D microrod array structure of NiMoO x ensures efficient H 2 bubble removal, leading to stable hydrogen production (Figure 5f).…”
Section: Micrometer Scalementioning
confidence: 99%
See 2 more Smart Citations
“…38,39 To address this challenge, our group synthesized a 0D/1D hierarchical heterostructure (MoNi/NiMnO x on a 3D porous NF) to enhance the efficiency of the hydrogen evolution reaction. 40 The catalyst effectively manages bubbles, displaying smaller and more rapidly dispersed H 2 bubbles than Pt/C (Figure 5e). The 1D microrod array structure of NiMoO x ensures efficient H 2 bubble removal, leading to stable hydrogen production (Figure 5f).…”
Section: Micrometer Scalementioning
confidence: 99%
“…In electrochemical processes, gas bubbles can impact reactions, hindering hydrogen production if excessively accumulated on the catalyst surface. , To address this challenge, our group synthesized a 0D/1D hierarchical heterostructure (MoNi/NiMnO x on a 3D porous NF) to enhance the efficiency of the hydrogen evolution reaction . The catalyst effectively manages bubbles, displaying smaller and more rapidly dispersed H 2 bubbles than Pt/C (Figure e).…”
Section: Multiscale Approach To Water Electrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Both theoretical predictions and experimental findings suggest that the HER activity of TMDs primarily stems from their edges rather than their basal planes. 35,36 Various techniques have been devised to improve the catalytic performance of TMDs, such as defect engineering, 37 heterostructure fabrication, 38 phase conversion 39 and foreign atom doping. 40 Wang et al synthesized metallic WSe 2 nanoscrolls used as electrocatalysts for the HER, demonstrating much enhanced electrocatalytic performance compared to the semiconducting 2H WSe 2 nanoscroll counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many efforts have recently been devoted to unraveling their structural–activity relationship and attaining exceptional catalytic activity and endurance under steady state conditions through dynamic dissolution and the construction of alloy-oxide interfaces. 7–10 However, the catalyst must be tolerant to intermittent fluctuating power, deliberate shutdowns and on–off cycles in a realistic scenario, which is of particular importance for green hydrogen production powered by renewable energy. 11,12 In an earlier work, Divisek et al 13 reported a profound deactivation of the Ni–Mo catalyst after a power interruption, accompanied by substantially lowering the Mo amount in the catalyst.…”
mentioning
confidence: 99%